Emerging Role of Long Non-Coding RNAs in the Pathobiology of Glioblastoma - Rezaei, Omidvar; Tamizkar, Kasra Honarmand; Sharifi, Guive; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Frontiers in Oncology, 2021)
Glioblastoma is the utmost aggressive diffuse kind of glioma which is originated from astrocytes, neural stem cells or progenitors. This malignant tumor has a poor survival rate. A number of genetic aberrations and somatic mutations have been associated with this kind of cancer. In recent times, the impact of long non-coding RNAs (lncRNAs) in glioblastoma has been underscored by several investigations. Up-regulation of a number of oncogenic lncRNAs such as H19, MALAT1, SNHGs, MIAT, UCA, HIF1A-AS2 and XIST in addition to down-regulation of other tumor suppressor lncRNAs namely GAS5, RNCR3 and NBAT1 indicate the role of these lncRNAs in the pathogenesis of glioblastoma. Several in vitro and a number of in vivo studies have demonstrated the contribution of these transcripts in the regulation of cell proliferation and apoptosis, cell survival, invasion and metastasis of glioblastoma cells. Moreover, some lncRNAs such as SBF2-AS1 are involved in conferring resistance to temozolomide. Finally, few circularRNAs have been identified that influence the evolution of glioblastoma. In this paper, we discuss the impacts of lncRNAs in the pathogenesis of glioblastoma, their applications as markers and their implications in the therapeutic responses in this kind of cancer.